Working in corona-designated departments in a fortified underground hospital: Concerns about corona and predictors of job burnout - Nashashibi, Lauren; Khouri, Marlyn; Meretyk, Irit; Livni, Tom; Cohen, Noga; Fruchter, Eyal (Frontiers in Psychiatry, 2023)
Background In August 2020 during Israel’s second COVID-19 wave Rambam Medical Center opened the Sammy Ofer Fortified Underground Emergency Hospital. This was declared a regional Corona center in the north of Israel, receiving the most severe Corona patients from the region. Alongside the advanced inpatient capacity and technology within the underground facility, there was a severe shortage of trained medical and paramedical staff, as well as harsh working conditions. The current study examined the implications and effects of working in an underground facility on healthcare workers, focusing on emotion regulation tendencies and profession as predictors of job burnout. Methods Seventy-six healthcare workers, who had worked in the underground hospital for a minimum continuous period of 2 weeks during the peak of the COVID-19 pandemic, and a control group of 40 healthcare workers from northern Israel were asked to fill out an online survey administered via Qualtrics (total sample 116). The survey comprised six questionnaires: a demographic survey questionnaire; a COVID-19 concerns questionnaire; a psychological distress questionnaire (DASS, Depression Anxiety Stress Scale); trait worry (PSWQ; Penn State Worry Questionnaire); emotion regulation (ERQ, Emotion Regulation Questionnaire), and burnout (SMBM, Shirom - Melamed Burnout Measure). Results Independent-samples t-tests revealed no significant differences in psychological distress or burnout between Rambam Underground hospital workers and the control group. Conversely, COVID-19 concern scores were significantly different in the two groups, the Rambam hospital workers showing less concern (M = 2.9, SD = 0.73) than the control group (M = 3.47, SD = 0.76) [t(114) = −3.974, p < 0.001]. Hierarchical linear regression analysis identified the significant predictors of burnout among healthcare workers. Participants’ profession (physician), psychological distress (total DASS score), and a personality trait of worry were statistically significant predictors for job burnout (p = 0.028, p < 0.001, p = 0.023, respectively). Concerns about COVID-19 marginally predicted job burnout (p = 0.09). Group (underground vs. control) and emotion regulation tendencies did not predict burnout. Conclusion The two groups showed no significant differences in psychological distress nor in burnout. Being a physician, having an intrinsic trait of being overly worried and experiencing psychological distress were significant predictors for job burnout among healthcare workers, regardless of work environment (underground vs. control).